Principles of research and development: a handbook for teaching basic concepts in new product development - Goddard, Kathryn (Kansas State University, 2012)
Food product development involves more than just creating the perfect recipe. Representatives from marketing, procurement, research and development, safety, and quality all work together to complete product development projects. This manuscript is aimed to serve food science students and professionals learning the basics of the product development process, food component functionality, basic units of food processing, regulatory considerations, food safety concepts, consumer testing, confidentiality/ intellectual property issues, and essential pieces of marketing. Many other texts concentrate on food product development, but this text looks to create a more comprehensive guide. The breadth of knowledge needed for food product development are vast. Food science students and professionals can use this text to provide basic (not exhaustive) knowledge necessary to be a valuable part of a new product development team.
Keywords: Product Development; Additives; Labeling; Food; Nutrition; Food Science (0359)